International Journal of Medical Students - Year 2013 - Volume 1 - Supplement 1 - Executive Committee of IJMS (University Library System, University of Pittsburgh, 2018)
International Journal of Medical Students - Year 2013 - Volume 1 - Supplement 1 The Sixth Young European Scientist Meeting Special Supplement